The Influence of Traditional Games on The Motor Development of Students with Disabilities - Gumilar Mulya (Jurnal Pendidikan Humaniora, 2020)
Abstract: The purpose of this study was to examine the effect of the application of traditional games on motor development in students with disabilities. The method used in this study is the experimental method. The sample that participated in this study in this study was 25 students with disabilities taken from three special needs kids schools with an average age of 12 years. The sampling technique used by the writer was purposive sampling. The data collected in this study used a preliminary test and a final test using a standing broad jump, long jump, and throwing test. The conclusion of the research shows that traditional games offer a significant difference in the motor development of children with disabilities.Key Words: traditional games, gross motor development, disabilities, physical educationAbstrak: Tujuan dari penelitian ini adalah untuk menguji pengaruh penerapan dari permainan tradisional terhadap perkembangan motorik pada siswa penyandang disabilitas. Metode yang digunakan pada penelitian ialah metode eksperimen, sampel yang berpartisipasi dalam penelitian sebanyak 25 orang siswa disabilitas yang diambil dari tiga sekolah SLB dengan usia rata-rata siswa 12 tahun. Teknik pengambilan data yang digunakan ialah purposive sampling. Pengumpulan data dalam penelitian menggunakan tes awal dan tes akhir dengan menggunakan tes standing broad jump, long jump, melempar. Simpulan penelitian menun-jukkan bahwa permainan tradisional memberikan perbedaan yang signifikan pada perkembangan motorik anak disabilitas.Kata kunci: permainan tradisional, perkembangan motorik kasar, disabilitas, pendidikan jasmani